EPID-28. WHAT DO PATTERNS OF "UNCLASSIFIED" BRAIN TUMORS TELL US ABOUT INCIDENCE RATES OF NON-MALIGNANT BRAIN TUMORS IN CANADA?. (11th November 2019) - Smith, Trenton; Walker, Emily; Yuan, Yan; Davis, Faith; Megyesi, Joseph
Abstract: BACKGROUND: Patients with non-malignant brain tumors (NMBT) can experience significant morbidity and mortality; the degree of which varies by histological subtype. A recent report on all primary brain tumors in Alberta (AB), British Columbia (BC), Manitoba (MB) and Ontario (ON) showed 19.1% of NMBT were categorized as 'unclassified'. Missing data on histological subtypes encumbers efforts to understand the burden of disease associated with NMBT. The purpose of this analysis was to examine the distribution of unclassified tumors across participating provinces to identify targets for improved surveillance. METHODS: Data were provided from cancer registries in AB, BC, MB, and ON. Age Standardized Incidence Rates (ASIR) and frequencies were estimated using SAS 9.4. Given data from the United States (U.S) is accurate and the population is comparable, ASIR of NMBT in the U.S were used as expected values in this analysis. The 2011 Canadian Population and the 2000 US population were used for standardization to compare within Canada and to U.S data respectively. RESULTS: The ASIR of total NMBT and was highest in ON, relative to other participating provinces and similar to that of the U.S (15.25 and 15.91 cases/100, 000 person-years, respectively). However, ON had an ASIR about 10 times higher than other provinces for unclassified tumors (ON:6.3 cases/100, 000 person-years; BC: 0.4 cases/100, 000 person-years; AB:0.3 cases/100, 000 person-years; and MB:0.6 cases/100, 000 person-years). When unclassified tumors were excluded from the analysis, the ASIR of NMBT was similar across participating provinces. CONCLUSIONS: Findings from this analysis indicate that the Ontario provincial cancer registry has complete data on total NMBT cases. However, the high ASIR of unclassified cases in the NMBT category indicates that quality control measures could be improved. Further examination of the unclassified cases in ON could be used to improve the accuracy of the ON cancer registry and the completeness of other province's registries.